A Simple Solubility Tests for the Discrimination of Acrylic and Modacrylic Fibers. Issue 3 (19th February 2014) - Suga, Keisuke; Narita, Yuji; Suzuki, Shinichi
Abstract In a crime scene investigation, single fibers play an important role as significant trace physical evidence. Acrylic fibers are frequently encountered in forensic analysis. Currently, acrylic and modacrylic are not discriminated clearly in Japan. Only results of FT‐IR, some of acrylics were difficult to separate clearly to acrylic and modacrylic fibers. Solubility test is primitive but convenient useful method, and Japan Industrial Standards (JIS) recommends FT‐IR and solubility test to distinguish acrylic and modacrylic fibers. But recommended JIS dissolving test using 100% N, N‐dimethylformamide (DMF) as a solvent, some acrylics could not be discriminated. In this report, we used DMF and ethanol (90:10, v/v) solvent. The JIS method could not discriminate 6 acrylics in 60 acrylics; hence, DMF and ethanol (90:10, v/v) solvent discriminated 59 of the 60 fibers (43 acrylic and 16 modacrylic fibers) clearly, but only one modacrylic fiber incorrectly identified as acrylic.